A Business Model Of Marketing Capabilities And Marketing Perform:Ances -The Case Of Micro-Enterprises (Mies) In Kedah - Mohamed, Baderisang (2009)
This need for a marketing capabilities model that is applicable to MiEs underlies the principal purpose of this research to identify what are the marketing capabilities applied in MIEs; to identify the marketing performance adopted by MIEs; to come out with a business model depicting the relationship between marketing capabilities and the marketing performance of , the MIEs; and to validate the proposed business model of MiEs. This study was done on a developing country market (Kedah, Malaysia) where no marketing capabilities study has yet been carried out. Initially, qualitative methodology was applied with the use of past literatures review, in-depth interview with owner/manager of MiEs and observation techniques. All findings from each category were later triangulated to form a proposed model framework. The conceptual framework considered the marketing capabilities practiced as the independent variables and marketing performance as consequences of marketing capabilities. Later, it was tested with the quantitative survey method. Hypotheses of the study were tested using SPSS tools. The findings of the study supported the hypotheses of the study and confirmed the applicability of the proposed marketing capabilities framework. The findings of this study are mostly consistent with the previous marketing capabilities studies undertaken in other places. This first synthesis model of marketing capabilities for MiEs, is still to be established as a generic model.